Myxoglobulosis of the Appendix: A Case Associated with Ruptured Diverticulum - Panagiotis Aroukatos; Dionysios Verras; Gerassimos P. Vandoros; Maria Repanti (Case Reports in Medicine)
We describe a case of the extremely rare entity of myxoglobulosis of the appendix from a 45-year-old white man who was operated urgently with the clinical diagnosis of acute appendicitis. Sectioning of the appendix revealed the presence in the dilated appendiceal lumen of numerous whitish opaque globules ranging in size from 0.2 to 0.7 cm in diameter. A ruptured diverticulum and several smaller ones were also found. On microscopic examination, the globules consisted of faintly eosinophilic laminations of mucin surrounding an amorphous granular core. The mucin was identified by positivity with histochemical mucin stains. After thorough microscopic examination of the appendix, our case was diagnosed as myxoglobulosis due to mucosal hyperplasia, associated with ruptured diverticulum and acellular extra-appendiceal mucin deposits.